A systematic literature review (SLR): analysis of budget management accountability in local government agencies - Alfred Labi; Paltiman Lumban Gaol; Satunggale Kurniawan (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2026)
Accountability in budget management in local government agencies is a crucial issue in public governance because it is directly related to fiscal transparency, the quality of public services, and public trust in local government. This study aims to analyze the construct of budget management accountability in the scientific literature, identify factors influencing its strengthening, and map the main challenges faced in the practice of local budget management. The study uses a systematic literature review approach by examining relevant scientific articles through a systematic search, selection, and synthesis process based on the main research themes. The results of the study indicate that accountability in local government budget management is shaped by the relationship between the quality of financial reporting, the effectiveness of audits and supervision, the digitalization of financial management systems, and information transparency and public participation in the budget process. The findings also show that strengthening accountability depends not only on administrative compliance, but also on institutional capacity, apparatus competence, and the quality of information infrastructure that supports local fiscal governance. This study contributes to strengthening the conceptual understanding of local government budget accountability as a multidimensional phenomenon, while providing an analytical basis for policy development and further research oriented towards more transparent, responsive, and sustainable budget governance.